High-Risk Drivers and Road-Safety Governance in Italy: A Behavioural and Policy Perspective - Anna Pettini; Teresa Nobile; Ester Macrì (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This study uses an integrated analysis of survey data from 1,060 participants to examine driver attitudes and behaviours regarding road safety in Italy. Cluster analysis identified distinct driver profiles and significant geographical disparities. A high-risk subgroup (25% of respondents) was found, characterized by high self-confidence and low responsibility; younger age emerged as a key correlate. The misalignment between perceived and actual safety highlights the need for evidence-based policies. The study advocates an integrated approach combining targeted education, data-driven enforcement, and strategic infrastructure investment to advance Vision Zero goals.
Keywords: 330; road safety governance; driver responsibility; public administration; Vision Zero; cluster analysis; policy design